Welcome to Westonci.ca, the Q&A platform where your questions are met with detailed answers from experienced experts. Discover precise answers to your questions from a wide range of experts on our user-friendly Q&A platform. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
x + 3y = 14
x + 3(3x - 14) = 14
x + 9x - 42 = 14
10x - 42 = 14
+ 42 + 42
10x = 56
10 10
x = 5.6
5.6 + 3y = 14
- 5.6 - 5.6
3y = 8.4
3 3
y = 2.7
(x, y) = (2.7, 5.6)
x + 3(3x - 14) = 14
x + 9x - 42 = 14
10x - 42 = 14
+ 42 + 42
10x = 56
10 10
x = 5.6
5.6 + 3y = 14
- 5.6 - 5.6
3y = 8.4
3 3
y = 2.7
(x, y) = (2.7, 5.6)
For this problem, you first plug y=3x-14 in to x+3y=4
The equation will thin look like this:
x+3(3x-14)-14
since the value of y is equal to 3x-14, that means that 3y=3(3x-14)
then you distribute 3 into 3x-14
it will look like this:
3*(3x)+3*(-14)
(9x)+(-42)
9x-42
now you should have written x+9x-42=14
next, combine like terms
x+9x-42=14
10x-42=14
+42 +42
10x=56
now, you divide 56 by 10
10x=56
10 10
x=5.6
okay, now that x has been solved for, we now need to find the value of y
the simplest way to go about this is to choose the equation that already has y by its-self.
y=3x-14
plug 5.6 in to x
y=3(5.6)-14
now solve for y
y=(16.8)-14
y=2.8
FINAL ANSWER
y=2.8
x=5.6
if you want to check your work, you can plug x and y into either equation
x+3y=14
(5.6)+3(2.8)=14
5.6+8.4=14
14=14
y=3x-14
(2.8)=3(5.6)-14
2.8=16.8-14
2.8=2.8
I hope this helps.
The equation will thin look like this:
x+3(3x-14)-14
since the value of y is equal to 3x-14, that means that 3y=3(3x-14)
then you distribute 3 into 3x-14
it will look like this:
3*(3x)+3*(-14)
(9x)+(-42)
9x-42
now you should have written x+9x-42=14
next, combine like terms
x+9x-42=14
10x-42=14
+42 +42
10x=56
now, you divide 56 by 10
10x=56
10 10
x=5.6
okay, now that x has been solved for, we now need to find the value of y
the simplest way to go about this is to choose the equation that already has y by its-self.
y=3x-14
plug 5.6 in to x
y=3(5.6)-14
now solve for y
y=(16.8)-14
y=2.8
FINAL ANSWER
y=2.8
x=5.6
if you want to check your work, you can plug x and y into either equation
x+3y=14
(5.6)+3(2.8)=14
5.6+8.4=14
14=14
y=3x-14
(2.8)=3(5.6)-14
2.8=16.8-14
2.8=2.8
I hope this helps.
Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Thank you for trusting Westonci.ca. Don't forget to revisit us for more accurate and insightful answers.